CONCEPTUAL PROVISIONS OF THE FORMATION OF THE EXECUTIVE CULTURE OF FUTURE MUSIC TEACHERS WITH THE MEANS OF THE UKRAINIAN FORTOPIAN - Mihalyuk, Alla (Educological discourse, 2020)
The article is devoted to the problem of forming the performing culture in the instrumental preparation of future music teachers. The urgency of developing this problem is exacerbated by a number of existing contradictions, namely: between the increasing demands for the cultural orientation of performing arts teachers of the future and the insufficient level of formation of their performing culture; between the powerful educational potential of Ukrainian piano art and its underutilization in the process of forming the performing culture of future music teachers. Of particular importance is the Ukrainian piano art in the formation of the performing culture of future music teachers,